PENGARUH PENGGUNAAN MEDIA GEOBOARD TERHADAP KEMAMPUAN MENGENAL KONSEP BENTUK GEOMETRI PADA ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 2 KOTA PEKANBARU - Sari, Nila Mayang; Chairilsyah, Daviq; ', Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research is to know the effect of use of geoboard media usage of the ability to know the concept of geometric shapes for children aged 5-6 years in TK Negeri Pembina 2 Pekanbaru City. The sample of population in this research is 5-6 years old to amount to 19 person’s. To collect the data is observation technis. To analysis data used in this research is test-t. The result of research is obtained from P value = 78%. The means of research the effect of geoboard media usage of the ability to know the concept of geometric shapes for children aged 5-6 years. The receive or reject hypothesis based on SPSS data windows for version 21 then can be seen from a comparison t value and t table is calculation of the test-t, seen that result t value -27,48 from the parties of absolutely price, so the minus (-) price cannot be used (Sugiyono, 2010). Then value 27,48. Dk=38 and the fault stage 5%=2,101, it can be seen the t price count greater than t table the first fault 5% (27,48>2,101). The mean Ho= were rejected and Ha=accepted. This research can be concluded that geoboard media can be a medium of learning in developing children’s ability to recognize the concept of geometric shapes. Geoboard media on the ability to recognize the concept of geometric shapes in children aged 5-6 years in TK Negeri 2 Pekanbaru City regency the effect as big as 63% . May mean that children’s ability to recognize the concept of geometric shapes influenced by other factors of 37%.Keywords: ability to recognize the concept of geometric shapes, geoboard media